PERAN PEREMPUAN ACEH PADA PENDIDIKAN DAN POLITIK: Studi kasus di lingkungan Universitas Muhammadiyah Aceh - Nurul Jeumpa (Jurnal Ilmiah Didaktika, 2016)
The demand of equal rights of women in different spheres of life is one of the important agenda which voiced loudly today. Women’s achievements and skills in various aspects of life indicates that there is no difference between women and men. The results of this study show that women's participation in education at the University of Muhammadiyah is very good. It can be seen from the active participation of women in various educational programs in order to succeed teaching and learning process. While the impact of political existence in the university environment Aceh still shows a very little impact. It can be seen from the role of two women in the field of politics at the University of Muhammadiyah Aceh. Basically, Islam never distinguish between women and men. Islam permits women’s role in politics.